Procedimientos De Laboratorio Clínico Durante La Pasantía En El Centro De Atención Clínica Central De Urgencias Veterinarias (2023)
Within the professional practice of a veterinary doctor is the area of pathology and clinical laboratory which includes procedures such as: taking samples, sample processing and analysis of the results of those tests diagnostics in order to be able to study the different clinical cases in small species (domestic, dogs - Canis lupus familiaris and cats - Felis catus).